REVOLUSI DIGITAL & DINAMIKA PERKEMBANGAN CRYPTOCURRENCY DITINJAU DARI PERSPEKTIF LITERATUR REVIEW - Uli Wildan Nuryanto; Pramudianto Pramudianto (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The spread of digital technology currently faster and influence on all of human dimension, including to the financial sector. The presence of cryptocurrency using blockchain technology has changed the previously system that has been used for a long period and it come a pros and cons. The system built using peer-to-peer cause the system no longer need the 3rd party that control the financial system and since the system decentralized. The nature of cryptocurrency which made as the same with gold characteristic such as the limitation of quantity, process to get it must through the mining process, more resistance from inflation are making people and society interested and significantly increase time by time. The decentralized and anonymous blockchain working system for token holders and safe has presented as a new paradigm in the financial sector. But on other hand, there are many challenges and dynamics that arise due to the emergence of these cryptocurrency, one of which is risk from the legal perspective where there are cases of money laundering involving of crypto, losses to the investor asset due to ICO process that not run smoothly, the emergence losses from crypto exchanges that hacked due to not have a high security backup system that made the customer losses their digital wallet. Crypto value that tend to have high volatility and fluctuating rates with fast count also increase the risk. The readiness of countries and drafting laws related to the crypto was contribution for this research. One of the biggest interested from the public is the use of crypto as long asset investment, where the values increasing from year to year, even Bitcoin as one of the cryptocurrencies that previously worthless but currently has very fantastic values and become a favourite from the investor